(untitled) (Research, Society and Development, 2021)
The concern with sustainability applies to water distribution networks, being responsible for transporting an increasingly valuable asset that is drinking water. These systems have on average high losses for various reasons. The focus here is the issue of over-pressure in the network caused by inefficient operation. Thus, investing in system improvements becomes essential. Thus, this work aims at proposing a procedure for operational strategies to control pressures to reduce water losses and parallel financial analysis. The methodology is based on hydraulic simulations of real area system with rugged topography establishing analysis scenarios and making economic analyzes. The study was done for an actual distribution network. The results showed that there were improvements in the control of pressures and consequent reduction of water losses in the scenarios with attribution of valves to sections, proposition of pumps, variation of levels of reservoirs among other propositions. It was concluded that the proposed procedure, although based on computational simulations can be considered important, since the experiment was done for a real system that represents an expressive set of systems found in operation.